2021
DOI: 10.1155/2021/9947047
|View full text |Cite
|
Sign up to set email alerts
|

Signal Pathways and Markers Involved in Acute Lung Injury Induced by Acute Pancreatitis

Abstract: Acute pancreatitis (AP) is a common acute abdominal disease with a mortality rate of about 30%. Acute lung injury (ALI) is a common systemic complication of acute pancreatitis, with progressive hypoxemia and respiratory distress as the main manifestations, which can develop into acute respiratory distress syndrome or even multiple organ dysfunction syndrome (MODS) in severe cases, endangering human health. In the model of AP, pathophysiological process of the lung can be summarized as oxidative stress injury, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…In severe cases, systemic inflammation and failure of the surrounding organs will occur [ 27 , 28 ]. The inflammatory response and oxidative stress play an indispensable role in SAP [ 20 , 22 ]. TXNIP is a multi-functional protein that acts as a signal conductor of the oxidative stress response [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In severe cases, systemic inflammation and failure of the surrounding organs will occur [ 27 , 28 ]. The inflammatory response and oxidative stress play an indispensable role in SAP [ 20 , 22 ]. TXNIP is a multi-functional protein that acts as a signal conductor of the oxidative stress response [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activated PSCs also secrete the neutrophil chemokine IL-8 and macrophage chemoattractant protein-1 (MCP-1) and express intracellular adhesion molecule-1 (ICAM-1) [ 36 , 37 ], suggesting that activated PSCs may be involved in exacerbating pancreatic inflammation by recruiting inflammatory cells. Studies have shown that pancreatic acinar cells secrete various inflammatory cytokines in response to the stimulation of pancreatitis [ 16 , 20 ]. The inflammatory response during SAP is characterized by the induction of a cascade of proinflammatory mediators which culminates in the recruitment of macrophages and neutrophils to the inflamed pancreas, thus leading to pancreatic acinar cell injury [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that melatonin alleviates lung inflammation caused by silica nanoparticles by downregulating TXNIP-related signaling pathways [11] . Therefore, TXNIP is an important molecule connecting various cellular functional pathways in oxidative stress and inflammation [12,13] . However, the role of TXNIP in SAP has yet to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…NLRP3, one of the NLR proteins, plays an important role in forming in ammasomes, which mediate caspase−1 activation and the secretion of the proin ammatory cytokine IL−1β in response to microbial infection and cellular damage [3]. It has been shown that NLRP3 in ammatory vesicles are activated not only in the pancreas but also in the intestine and lungs of rats with AP, and that the degree of activation correlates with the severity of AP [4] [5]. Effective inhibition of the NLRP3 pathway has emerged as an effective means of treating the in ammatory response to AP.…”
Section: Introductionmentioning
confidence: 99%